Activation of the pentose phosphate pathway by microcurrent stimulation mediates antioxidant effects in inflammation-stimulated macrophages - Uemura, Mikiko; Maeshige, Noriaki; Yamaguchi, Atomu; Ma, Xiaoqi; Fu, Yunfei; Inoue, Taketo; Matsuda, Mami; Nishimura, Yuya; Hasunuma, Tomohisa; Wang, Ji; Kondo, Hiroyo; Fujino, Hidemi (Frontiers in Physiology, 2025)
IntroductionExcessive inflammatory responses in macrophages lead to increased oxidative stress, and the excessive production of reactive oxygen species (ROS) causes tissue damage, contributing to the development of chronic diseases and tissue deterioration. Therefore, controlling the inflammatory response and ROS production is crucial for human health. Electrical stimulation (ES) has been shown to have antioxidant and anti-inflammatory effects on macrophages. However, the key pathway underlying these effects remains unclear.MethodsIn this study, ES was applied to Lipopolysaccharide (LPS)-stimulated macrophages, and the production of ROS and 8–hydroxy–2′–deoxyguanosine (8-OHdG), inflammatory cytokine expression, and intracellular metabolites were analyzed in a glucose-6-phosphate dehydrogenase (G6PD) knockdown experiment, the rate-limiting enzyme of the Pentose Phosphate Pathway(PPP).ResultsES significantly increased sedoheptulose 7-phosphate (S7P), an intermediate metabolite in PPP, and reduced ROS and 8-OHdG production and the expression of inflammatory cytokines in LPS-stimulated macrophages. Meanwhile, ES did not exert antioxidant effects in G6PD-knockdown macrophages.DiscussionThese findings indicate that the antioxidant effects of ES are mediated by PPP in LPS-stimulated macrophages.